Psychometric Analysis of the Brief Resilient Coping Scale (BRCS) in University Students from Lima, Peru - Alegre Bravo, Alberto (2026)
The present study aimed to evaluate the psychometric properties of the Brief Resilient Coping Scale (BRCS) in a sample of university students from Lima, Peru. A total of 866 students participated (38.3% men and 61.7% women), aged between 18 and 50 years (M = 22.06; SD = 4.97), selected through non-probabilistic convenience sampling. The BRCS was administered online together with a sociodemographic questionnaire. Descriptive analyses showed adequate item distributions, with skewness and kurtosis indices within acceptable ranges and corrected item–total correlations above .30. Confirmatory factor analysis, estimated using the DWLS method, supported the unidimensional structure of the scale, with factor loadings ranging from .641 to .836 and excellent model fit (CFI and TLI = 1.00; RMSEA = .0016; SRMR = .005). Reliability was satisfactory (α = .751; ω = .761), and convergent validity was acceptable (AVE = .504). In addition, factorial invariance across sex and type of university was confirmed. These findings support the use of the BRCS as a brief and robust measure for assessing resilient coping, with relevant applications in research and in the design of initiatives aimed at promoting psychological well-being in university settings.